2005
DOI: 10.1111/j.1439-0396.2005.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Site and extent of starch degradation in the dairy cow – a comparison between in vivo, in situ and in vitro measurements

Abstract: Prediction of the supply of glycogenic precursors to dairy cows and the site of degradation of wheat, maize and potato starch (PS) were determined in an in vivo experiment and the results were compared with data obtained from experiments involving in situ nylon bag and in vitro gas production techniques. In a Latin square design experiment four lactating dairy cows fitted with a rumen cannula and T-piece cannulae in the duodenum and terminal ileum, received either a low-starch control diet or diets in which su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 17 publications
7
40
0
1
Order By: Relevance
“…Wheat and sugar beat pulp contained 557 and 5 g/kg of DM starch, respectively, with 52 and 0 g/kg of DM bypass starch, respectively (CVB, 2007). Wheat starch degradation in the rumen was 89.6% in a study by Hindle et al (2005). Water intake, DMI, and milk yield were recorded daily.…”
Section: Experimental Treatments and Dietsmentioning
confidence: 99%
“…Wheat and sugar beat pulp contained 557 and 5 g/kg of DM starch, respectively, with 52 and 0 g/kg of DM bypass starch, respectively (CVB, 2007). Wheat starch degradation in the rumen was 89.6% in a study by Hindle et al (2005). Water intake, DMI, and milk yield were recorded daily.…”
Section: Experimental Treatments and Dietsmentioning
confidence: 99%
“…Above all, in vitro and in vivo studies are usually performed separately under different conditions and there is a lack of direct in vitro-in vivo comparison, which is essential to demonstrate the robustness or effectiveness of the in vitro GP technique in simulating rumen fermentation. Hindle et al (2005) compared the in vitro and in vivo starch degradation from different sources and found a discrepancy between the in vivo starch degradation and that estimated from an in vitro GP experiment in which the donor animals were not adapted to the diets with the same starch source. The authors suggested in vitro GP could provide a more accurate simulation of the in vivo fermentation of potato starch if the donor animals are adapted to a diet including this starch source.…”
Section: Introductionmentioning
confidence: 99%
“…Information on the relationship between chemical composition and in situ rumen degradation characteristics of dry matter (DM), organic matter (OM), CP, starch and neutral detergent fiber (NDF) of maize silages in the scientific literature is scarce. Several in situ studies have been conducted on maize silages to determine the effect of individual factors such as maturity stage (Johnson et al, 1999;Di Marco et al, 2002;Jensen et al, 2005), chop length (Fernandez et al, 2004) and ensiling (González et al, 2010) of maize crop on the rumen degradation of specific nutrients like DM (Von Keyserlingk et al, 1996), OM (Arieli et al, 1998), CP (Von Keyserlingk et al, 1996;Shannak et al, 2000), starch (Fernandez et al, 2004;Hindle et al, 2005) and NDF (Varga and Hoover, 1983;Stensig et al, 1994;Jensen et al, 2005). In addition, often in these studies only a limited number (n = 1 to 12) of samples were investigated and compared with other feedstuffs.…”
Section: Introductionmentioning
confidence: 99%